2018
DOI: 10.1002/pssr.201800517
|View full text |Cite
|
Sign up to set email alerts
|

New One‐Dimensional Material Nb2Se9: Theoretical Prediction of Indirect to Direct Band Gap Transition due to Dimensional Reduction

Abstract: Layered two‐dimensional (2D) transition metal dichalcogenides (TMDCs) often form 2D sheets and some of these show an indirect to direct band gap transition as the number of layers decreases from that of the bulk structure. Recently, a new one‐dimensional (1D) material of Nb2Se9 is successfully prepared by solid state reaction. This material is semiconducting and composed of periodically stacked single‐chain atomic crystals (SCAC) where the SCACs form inorganic bulk crystals due to strong bonds within the chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 63 publications
(104 reference statements)
1
26
0
Order By: Relevance
“…35 These phenomena are mainly caused by vdW interchain interactions. Previous studies of metal chalcogenides used only the generalized gradient approximation method, 35,47,48 which cannot properly describe vdW effects; therefore, further calculations were performed to incorporate vdW interactions. 36,49 We chose the DFT-D3 method, which introduces the dispersion energy correction proportional to 1/ r 6 .…”
Section: Structures and Computational Methodsmentioning
confidence: 99%
“…35 These phenomena are mainly caused by vdW interchain interactions. Previous studies of metal chalcogenides used only the generalized gradient approximation method, 35,47,48 which cannot properly describe vdW effects; therefore, further calculations were performed to incorporate vdW interactions. 36,49 We chose the DFT-D3 method, which introduces the dispersion energy correction proportional to 1/ r 6 .…”
Section: Structures and Computational Methodsmentioning
confidence: 99%
“…[18][19][20][21] Moreover, it was theoretically confirmed that some of the 1D vdW materials exhibit thickness-dependent properties, such as the bandgap expansion with the indirect-to-direct transition as the number of unit chains decrease from their bulk crystal, similar to well-studied transition metal dichalcogenides (TMDs). [22][23][24][25] Based on this aspect, numerous studies have been conducted to utilize 1D nanowires in functional electronic devices such as FET [26][27][28][29] and photodetectors, [30][31][32][33] but diversity among promising materials is still limited. Therefore, it is necessary to discover new types of 1D materials, verify their electronic properties, and expand the potential candidates for future electronic device applications.…”
Section: Introductionmentioning
confidence: 99%
“… 23 The weak van der Waals forces are responsible for the easy sliding of the layers relative to one another, thus providing a favourable matrix for intercalation reactions and exfoliation. 24 The coordination around the Nb atom can either be a distorted octahedral or trigonal prismatic. 23 On the other hand, Nb 2 Se 9 is a new 1D material made up of periodically stacked single-chain atomic crystals, which form the inorganic bulk of the crystals due to strong covalent bonds within the chain and weak van der Waals interaction between the chains, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%